Algunos lineamientos para la conservación de Cittarium pica en la costa Caribe del Darién colombiano (2008)
ABSTRACT:The overexpoilment of whelk (Cittarium pica) in the northwestern coast of Acandí (Capurganá and Sapzurro), in the Chocoan Urabá, has generated the necessity to know the relationship of the coastal population with this resource and its attitude onwards sustainable management, facing the conservation of this emblematic marine snail in the local culture. Basic methods were founded on Participatory Action Research (PAR) developed by participatory meetings, open interviews and participatory observation (field notebooks). The abundance of whelk can be see in danger in situations of low salinity, or by the excess of direct captures or the challenges derived from the industrial fishing. Since 1974, in Capurganá, the feast of cigua is an occasion to gather tourism arround typical cooked preparations of cigua. However, the fluctuations in the abundance of the snail show that the community has to adapt of a series of decisions on how much use and how much conservation is required in the present management.